Degrowth as an alternative to sustainable tourism: an exploring study of tourists´ relationship with sustainability and degrowth - Barboza, Miriam Rueda Nery (2024)
This dissertation explores tourists' relationship with degrowth and sustainability, in the perspective of degrowth as an alternative to sustainable tourism. Through a mixed-methods approach of online survey data collection, statistical factor and cluster analysis, and word cloud visualization, the study identifies the main dimensions of tourist behavior and types of tourists according to their knowledge and alignment with sustainability and degrowth principles in tourism. Findings reveal that degrowth is a very unknown concept among tourists and that the group of tourists most aligned with its principles were those with more sustainable behavior. The younger tourists did not show sustainable travel behavior and seemed to be opposed to degrowth principles. This research highlights the potential of degrowth to address sustainability issues in the context of tourism and the importance of involving tourists and communities in the process of change towards more sustainable tourism.